THE STUDY ON FIBROUS PROTEIN OF PIG SCALP ENRICHMENT PRODUCTION TECHNOLOGY - A, Bayanzul; L, Damdinsuren; A, Gombojav; N, Chimegee (Mongolian Journal of Agricultural Sciences, 2018)
Studying the chemical composition of pig scalp and extracting the fibrous protein supplements, and completed a study on the use of it in the enrichment technology for sausage production. In addition, there is being used an advanced method to accelerate biochemical reactions to be transmitted into gluten form which is contained in a pig scalp for collagen protein through collagenase enzyme serving. It’s confirmed as the optimal sublimation procedure to use collagenase ferment as a catalyst and cook the pork scalp at 95-97°C for 2-2.5 hours to extract protein concentrator, which will be then frozen at -86°C for 13 hours before being dried in an environment with temperature at -54°C and pressure P=28.9Pa for 8 hours. It’s the most optimal solution if the fibrous protein concentrator is used at 5% of meat mass to be used in the boiled sausage. Research results have shown that dried fibrous protein and its collagen preparation is having with a protein-rich /32.6%/ and low moisture /23.59%/, are proves that is a worthy product to offset the deficiencies of protein collagen forthe human body and to be having with a length of storage time.